A Mechanistic Study on the Non-genotoxic Carcinogenicity of the Food Contaminant Semicarbazide - Daniel P. Fitzpatrick (SURE Journal: (Science Undergraduate Research Experience Journal))
Semicarbazide was brought to the forefront of scientific discussions by the scientific community in the early 2000’s as the substance was discovered in several food products from both synthetic and natural sources. Although semicarbazide was processed through several toxicological assays and classified as a non-genotoxic carcinogen, underwhelming amounts of toxicological data exists for the compound. The present study is one of the first in-vitro studies to examine the relationship between sub-pathophysiological concentrations of reactive oxygen species and the anomalous non-genotoxic carcinogenicity induced by semicarbazide through the upregulation of intracellular signalling pathways. A novel finding of the present study was where NRK cells were exposed to micromolar concentrations of semicarbazide, an inverse relationship between protein kinase C activity, and free radical concentration proportionally increases > 2-fold. It is the hypothesis of the present study that the >2-fold increase in free radical concentration and upregulation of protein kinase C from the 0.01mM treatment of semicarbazide has the capacity to alter physiological signalling mechanisms into a sub- pathophysiological state. These changes in the cellular environment could be the initiation mechanism that facilitates the manifestation of cancer in a cell population. The induced upregulation of protein kinase C activity within NRK cells by semicarbazide can be extrapolated to downstream mediators of the Ca2+ dependent signalling pathway and the mitogen activated protein kinase signalling pathway. The hypothesis of the present study concludes by highlighting the importance of these pathways in the manifestation of semicarbazide induced non-genotoxic carcinogenicity. In conclusion, this study classifies semicarbazide as an intracellular signalling mitogen based on its capacity to modulate protein kinase C activity and the concentrations of intracellular reactive oxygen species.